2003
DOI: 10.1002/app.12092
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy characterization of ultrathin polystyrene films formed by admicellar polymerization on silica disks

Abstract: Atomic force microscopy was used to study the characteristics of polymer films formed via admicellar polymerization (the polymerization of monomers solubilized in adsorbed surfactant aggregates). The investigated system included cetyltrimethylammonium bromide (C 16 TAB) as a cationic surfactant, styrene, 2,2Ј-azobisisobutyrilnitrile as an initiator, and polished silica disk substrates. Our goal was to examine changes in the properties and morphology of the formed polymer films due to changes in the surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…It has been shown that the level of adsolubilization impacts the physical and cure properties of admicellar polymerization modified silica-reinforced rubber compounds [7,[21][22][23]. More recently the impact of the levels of adsorbed surfactant and adsolubilized monomer on the polymer formed during admicellar polymerization has been examined on flat and amorphous silica surfaces [18,19]. Results on both surfaces show that the distribution, thickness, and morphology of the formed polymer are very strongly determined by the amount of added monomer, and somewhat determined by the amount of adsorbed surfactant [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the level of adsolubilization impacts the physical and cure properties of admicellar polymerization modified silica-reinforced rubber compounds [7,[21][22][23]. More recently the impact of the levels of adsorbed surfactant and adsolubilized monomer on the polymer formed during admicellar polymerization has been examined on flat and amorphous silica surfaces [18,19]. Results on both surfaces show that the distribution, thickness, and morphology of the formed polymer are very strongly determined by the amount of added monomer, and somewhat determined by the amount of adsorbed surfactant [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the formed polymer thin film has been examined using ellipsometry [5], scanning electron microscopy [17], and tapping mode atomic force microscope at ambient condition [18,19]. However, without an understanding of the behavior of the multicomponent adsorbed layer, the structure and properties of the formed polymer film cannot be predicted or effectively controlled [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] More recently, the examination of polymer formation via admicellar polymerization has been studied using atomic force microscopy (AFM) that allows the film to be studied at the nanometer scale. [29][30][31] AFM has been used to probe the nature of surfactant-modified mica surface morphologies. [31][32][33] The AFM tip can interact with the sample surface at the atomic level.…”
Section: Introductionmentioning
confidence: 99%